Rheumatic Heart Disease Burden and Need of Cardiovascular Surgery Service in Bharatpur Hospital - Gautam, Mani Prasad; Acharya, Keshab Prasad (Journal of National Heart and Lung Society Nepal, 2022)
Background: Rheumatic heart disease is one of the major public health concerns in Nepal. Depending on the severity of valvular involvement, these cases are managed either medically or surgically. As our centre is planning to develop cardiovascular surgery, we wanted to study the burden of valvular cases requiring on surgical management in our hospital.Methods: A cross-sectional study was conducted in the Department of Cardiology, Bharatpur Hospital, Chitwan, Nepal. During one year 4636 echocardiography conducted, 220 rheumatic heart disease cases were identified and included in the study.Results: The Mean±SD age was 24.5±12.4 years. Eighty percent subjects had valvular lesions suitable for medical management. Twenty percent subjects had severe valvular lesions requiring surgery or intervention. Out of these, only 30 subjects (13.6%) were operable, 4 (2.2%) were severe mitral stenosis cases suitable for balloon valvotomy and 10 subjects (4.5%) were unfit for surgery because of reduced ejection fraction.Conclusion: The majority of rheumatic heart disease were manageable by medical treatment. Small proportion of subjects required surgical management and a few of them were fit for balloon valvotomy. We conclude that the development of cardiovascular surgery setup in our hospital is a must and certainly will upgrade the rheumatic heart disease management.